Prevalence of suicidality in the European General Population: A systematic review and meta-analysis. - Castillejos, María del Carmen; Huertas Maestre, Paloma; Martin, Paloma; Moreno-Kustner, Berta (My University, 2020)
Objective: To conduct a systematic review and meta-analysis of the prevalence and variability in suicidality in the general adult population of Europe between 2008 and 2017. Methods: Studies containing original data on suicidality were identified in five electronic databases. Point, 12-month and lifetime prevalences were calculated for various types of suicidality. Pooled prevalence rates were calculated using a random effects model. Subgroup analysis and multivariate meta-regression were also performed. Results: We identified 24 papers containing original data, which provided 97 prevalence rates for suicidality. The pooled point prevalence rate was 3.96% (2.37–5.56), pooled 12-month prevalence 2.9% (1.49–4.32), and pooled lifetime prevalence 5.55% (4.31–6.79). The subgroup analysis showed that lifetime prevalence figures for wishing to be dead and suicidal ideation were higher in areas with a population of less than 3,849 inhabitants and in Eastern Europe. Finally, the multivariate meta-regression showed differences with respect to the period and type of suicidality, lower and upper age thresholds, population size, and study area. Conclusion: Our data showed that approximately 21% of European individuals have wished to be dead at some point during their lifetime. Studies like this are necessary to highlight the need for efforts to prevent and intervene in suicidality.
Keywords: Suicidio - Europa - 2008-2017; Epidemiology; Suicidality